Green Pesantren: Best Practice of Integrating Green Technology and Sustainable Agriculture for Eco-friendly Education - Wawan Saepul Bahri; Maswani Maswani; Nur Kafid; Rifqi Miftahul Amili; Ahmad Masruri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Unwise use of the environment has triggered various global problems, such as natural destruction, declining biodiversity, climate change, and the depletion of natural resources, which are indicators of crisis, including in Indonesia. This study aims to examine the application of green technology and sustainable agricultural systems at the Pangrango Nature Islamic Boarding School in West Java. The method used is a qualitative approach, with data collected through in-depth interviews with purposively selected informants, supported by document analysis, and tested through triangulation to ensure the validity and reliability of the findings. The results of the study show that the application of green technology and sustainable agriculture is realized through various real practices, such as the manufacture of organic liquid fertilizer from waste fermentation, the management and recycling of organic and non-organic waste, the application of vertical agriculture, and the use of mulch on beds to maintain soil fertility. This practice is not only effective in environmental management but also a means of contextual learning for students in understanding the importance of nature conservation. In addition, these findings expand understanding of the Bronfenbrenner and Jean Piaget habituation theory, which asserts that individual development occurs through dynamic interactions with the surrounding environment. The implications of this research underscore the importance of integrating green technology practices and sustainable agriculture into the Islamic boarding school education system, ensuring that learning is not only theoretical but also practical and contextual. In terms of the model, this research proposes a practice-based green pesantren, an educational model that emphasizes the habituation of environmentally friendly behavior and the integration of curriculum and field practice, and can be applied in other pesantren to form a generation that cares about environmental sustainability.